Pengaruh model pembelajaran kooperatif tipe team games tournament (TGT) terhadap kemampuan komunikasi matematis kelas VIII SMPN Masbagik Tahun Ajaran 2024/2025 - Hijriati, Awwalus sanatil; Arjudin; Wulandari, Nourma Pramestie; Baidowi (FKIP Universitas Mataram, 2025)
This study aims to determine the effect of the Team Game Tournament (TGT) type cooperative learning model on the mathematical communication skills of 8th-grade students at SMPN 6 Masbagik. The research employed a quantitative approach using a true experimental method with a posttest only control group design. The population consisted of all 8th-grade students at SMPN 6 Masbagik in the 2024/2025 academic year, totaling 76 students. The sample was selected using a cluster random sampling technique, with two classes selected from three, namely classes VIIIA and VIIIB, each consisting of 26 students. The two classes received different treatments: class VIIIA as the experimental class using the TGT learning model, and class VIIIB as the control class using conventional learning. Data were collected through a mathematical communication skills test and observation. Data analysis included normality and homogeneity tests, hypothesis testing using the Independent Sample t-Test, and an effect size test. The results showed that the average posttest score in the experimental class was 69.5, while the control class scored 55. The t-test result showed a t-count of 4.434 > t-table 2.008, indicating a significant difference. The effect size result of 1.09 falls into the large category. In conclusion, the TGT model significantly affects students' mathematical communication skills.